Correlative Light‐Electron Microscopy Shows RGD‐Targeted ZnO Nanoparticles Dissolve in the Intracellular Environment of Triple Negative Breast Cancer Cells and Cause Apoptosis with Intratumor Heterogeneity. Issue 11 (25th April 2016) - Othman, Basmah A.; Greenwood, Christina; Abuelela, Ayman F.; Bharath, Anil A.; Chen, Shu; Theodorou, Ioannis; Douglas, Trevor; Uchida, Maskai; Ryan, Mary; Merzaban, Jasmeen S.; Porter, Alexandra E.
Abstract : ZnO nanoparticles (NPs) are reported to show a high degree of cancer cell selectivity with potential use in cancer imaging and therapy. Questions remain about the mode by which the ZnO NPs cause cell death, whether they exert an intra‐ or extracellular effect, and the resistance among different cancer cell types to ZnO NP exposure. The present study quantifies the variability between the cellular toxicity, dynamics of cellular uptake, and dissolution of bare and RGD (Arg‐Gly‐Asp)‐targeted ZnO NPs by MDA‐MB‐231 cells. Compared to bare ZnO NPs, RGD‐targeting of the ZnO NPs to integrin αvβ3 receptors expressed on MDA‐MB‐231 cells appears to increase the toxicity of the ZnO NPs to breast cancer cells at lower doses. Confocal microscopy of live MDA‐MB‐231 cells confirms uptake of both classes of ZnO NPs with a commensurate rise in intracellular Zn 2+ concentration prior to cell death. The response of the cells within the population to intracellular Zn 2+ is highly heterogeneous. In addition, the results emphasize the utility of dynamic and quantitative imaging in understanding cell uptake and processing of targeted therapeutic ZnO NPs at the cellular level by heterogeneous cancer cell populations, which can be crucial for the development of optimized treatment strategies. Abstract : A fluorescently labeled RGD‐targeted ZnO nanoparticle (ZnO‐GFP‐HCV‐RGD NP) is developed for targeted delivery of ZnO to integrin αvβ3 receptors expressed on triple negative breast cancer cells (TNBCs). Correlative light‐electron microscopy shows ZnO‐GFP‐HCV‐RGD NPs dissolve in the intracellular environment of TNBCs and cause apoptosis with intratumor heterogeneity. More importantly, these NPs provide a possible strategy for targeted breast cancer therapy.